Strain partitioning enables excellent tensile ductility in precipitated heterogeneous high-entropy alloys with gigapascal yield strength. (September 2021) - He, Feng; Yang, Zhongsheng; Liu, Shaofei; Chen, Da; Lin, Weitong; Yang, Tao; Wei, Daixiu; Wang, Zhijun; Wang, Jincheng; Kai, Ji-jung
Abstract: High entropy alloys (HEAs) with grain-scale heterogeneous structure and coherent precipitates have shown gigapascal strength and considerable ductility. However, the origins of the excellent ductility of the HEAs with both precipitates and grain-scale heterogeneous structures are relatively less explored and not well understood. It is also still challenging to obtain such precipitated heterogeneous HEAs through efficient and economical thermomechanical processing procedures. Here, through single-step heat treatment, we developed a Ni2 CoCrFeTi0.24 Al0.2 HEA with an excellent yield strength of ~1.3 GPa and tensile elongation of ~20%. Using multiple length-scale microstructure characterizations and micro-digital image correlation analysis, we revealed the strengthening and toughening mechanisms of the novel HEA. Our results showed that the grain-scale heterogeneous structure with L12 precipitates ranging from ~10 to 100 nm is responsible for the excellent strength-ductility combination. The good ductility is attributed to the strain-partitioning-induced additional deformation modes, i.e., deformation twinning and microbands, as well as the efficient hetero-deformation induced strain hardening effect. The superior yield strength is mainly due to the effective combination of precipitation hardening and dislocation strengthening. These findings not only provide a facile route to develop strong and ductile alloys but also deepen the understanding of the deformation mechanism of hetero-structured materials. Highlights: A precipitated heterogenous HEA with yield strength of ~1.3 GPa and tensile elongation of ~20% was developed. The heterogenous structure and coherent precipitates were obtained within the same single-step heat treatment. The excellent ductility was attributed to additional deformation modes, i.e. deformation twins and micro-bands, and HDI strain hardening. With the aid of micro-DIC analysis, strain partitioning was asserted to be the intrinsic origin of the interesting deformation mechanism. Effective combination of precipitation hardening and dislocation strengthening is the main reason for high yield strength.